(Re-)Performing Early Mixed Music from the 1980s at Ircam: Pierre Boulez’s Dialogue de l’ombre double - Akkermann, Miriam (Circuit, 2016)
In the 1980s, performing mixed music required cumbersome, expensive technical equipment which was usually tied to institutions. Hence, the creation of those works was bound to technical structures, personnel resources, and facilities, and closely connected to technological developments. Today, re-performances of these works face several challenges. Due to rapidly changing technology, the performance of these pieces is in constant flux, and documentation on them is based in part on an oral tradition of information exchange. The career of such works is therefore more strongly connected to institutional actors than is typically the case. Based on the example of Pierre Boulez’s composition Dialogue de l’ombre double (1976/1981-1984), the situation of re-performances of mixed music compositions at Ircam in the 2000s is described in order to give a brief overview of more general trends.